2014
DOI: 10.1107/s1600536814010769
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Bis(3-tert-butyl-2-hydroxy-5-methoxybenzyl)hexahydropyrimidin-5-ol monohydrate

Abstract: The asymmetric unit of the title compound, C28H42N2O5·H2O, consists of one half of the organic mol­ecule and one half-mol­ecule of water, both of which are located on a mirror plane which passes through the central C atoms and the hydroxyl group of the heterocyclic system. The hydroxyl group at the central ring is disordered over two equally occupied positions. The six-membered ring adopts a chair conformation, and the 2-hy­droxy­benzyl substituents occupy the sterically preferred equatorial positions. The aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
2
4
1
Order By: Relevance
“…These interactions stabilize the molecular conformation, with O1Á Á ÁN1 = 2.696 (5) and O2Á Á ÁN2 = 2.702 (5) Å . These distances are closely comparable to those observed in the related structure (II) (Rivera et al, 2014). The molecular structure of the title compound.…”
Section: Structural Commentarysupporting
confidence: 85%
See 3 more Smart Citations
“…These interactions stabilize the molecular conformation, with O1Á Á ÁN1 = 2.696 (5) and O2Á Á ÁN2 = 2.702 (5) Å . These distances are closely comparable to those observed in the related structure (II) (Rivera et al, 2014). The molecular structure of the title compound.…”
Section: Structural Commentarysupporting
confidence: 85%
“…The N2-C7 distance of 1.485 (6) Å is slightly longer than the typical value for an N-C bond [1.469 Å ]. The remaining C-N bonds in the molecule are also typical and compare well with those found in the the related structure (II) (Rivera et al, 2014). The C12-O1 and C22-O2 distances are typical of those for a hydroxy substituent on an aromatic ring [1.376 (6) and 1.374 (5) Å , respectively].…”
Section: Figuresupporting
confidence: 72%
See 2 more Smart Citations
“…This red shift of the O-H stretching wavenumber is due to strong inter-or intramolecular hydrogen bonding, which is in agreement with our previous X-ray structural research in which two intramolecular hydrogen bonds were observed in the molecular structure of 1,3-bis(3-tert-butyl-2hydroxy-5-methoxybenzyl)hexahydropyrimidin-5-ol (2b) monohydrate. 10 The IR spectra of the compounds also showed a characteristic absorption band with a strong intensity of the C-O stretching of phenol, which appears at 1219 cm -1 , and an absorption band at approximately 1100 cm -1 , which is characteristic of the a polarized C-N bond. The formation of a hydrogen bond between this group and the adjacent phenolic group is responsible for the low absorption frequency, therefore confirming the formation of Mannich bases.…”
Section: Resultsmentioning
confidence: 90%